Room temperature electroluminescence from mechanically formed van der Waals III–VI homojunctions and heterojunctions - Balakrishnan, Nilanthy; Kudrynskyi, Zakhar R.; Fay, Mike W.; Mudd, Garry W.; Svatek, Simon A.; Makarovsky, Oleg; Kovalyuk, Zakhar D.; Eaves, Laurence; Beton, Peter H.; Patanè, Amalia (Wiley, 2014)
Room temperature electroluminescence from semiconductor junctions is demonstrated. The junctions are fabricated by the exfoliation and direct mechanical adhesion of InSe and GaSe van der Waals layered crystals. Homojunction diodes formed from layers of p- and n-type InSe exhibit electroluminescence at energies close to the bandgap energy of InSe (Eg= 1.26 eV). In contrast, heterojunction diodes formed by combining layers of p-type GaSe and n-type InSe emit photons at lower energies, which is attributed to the generation of spatially indirect excitons and a staggered valence band lineup for the holes at the GaSe/InSe interface. These results demonstrate the technological potential of mechanically formed heterojunctions and homojunctions of direct-bandgap layered GaSe and InSe compounds with an optical response over an extended wavelength range, from the near-infrared to the visible spectrum.